Performance Analyses of the Radio Orbital Angular Momentum Steering Technique Based on Ka-Band Antenna. (20th June 2017) - Lin, Mingtuan; Gao, Yue; Liu, Peiguo; Guo, Zhiqing
Abstract : The misalignment in the orbital angular momentum- (OAM-) based system would distort the radiation patterns of twisted beams carrying OAM, consequently making the OAM-based communication infeasible. To tackle the misalignment problem, a radio OAM steering technique based on a uniform circular array (UCA) is illustrated. Subsequently, simulations are conducted to explore the influence of the OAM steering on the OAM mode quality and transmission performance. Furthermore, UCAs working at Ka-band with formulated feeding networks are designed and fabricated to analyze the performance of the OAM steering. The influences of OAM steering on mode quality and orthogonality are then evaluated in the experiment. Overall, the analyses of OAM steering technique are beneficial for the development of radio OAM study.